Temperature Controller for Continuous Stirred Tank Reactor using Adaptive PSO Based PID Controller (International Journal of Engineering and Computer Science, 2018)
The objective of the project is to control the reactant temperature of a Continuous Stirred Tank Reactor (CSTR) by manipulating the coolant temperature. The plant is modeled mathematically for the normal operating condition of CSTR. Then the transfer function model is obtained from the process. The various different kinds of controller is designed and implemented to control the temperature of the CSTR system, such as conventional method (Trial and Error method), Ziegler- Nichols method, Fuzzy logic method, PSO tuned PID controller method and Adaptive PSO tuned PID controller method. The servo response is obtained for the different operating condition of temperatures. From the servo response, Adaptive PSO algorithm based PID tuning method has given better setpoint tracking capability than the Ziegler-Nichols method, Conventional PID method, Fuzzy logic method, Particle swarm optimization (PSO) algorithm based PID tuning method. . In particular, our experience supports the conjecture that Adaptive PSO algorithm based optimal tuning of PID controller method offer advantages over all other controller method